And so it happens: This Poet’s Response to Pop-Up Poetry - Everest, Beth (Imagining SoTL, 2024)
As a follow-up to my previous article in Imagining SoTL, entitled “The Word: What’s in It,” this reflection further explores the relationship in the art of Pop-Up Poetry, specifically the emotional impact for both the poet and the participant.